The tectonostratigraphic latitudinal record of the eastern Red Sea margin - Baby Guillaume; Delaunay Antoine; Aslanian Daniel; Afifi Abdulkader M. (BSGF - Earth Sciences Bulletin, 2024)
We characterize the eastern Red Sea necking crustal domain through its north-south structural and stratigraphic record. Along-strike margin segmentation occurred during rifting (∼28-14 Ma), with tilted blocks filled by siliciclastic sediments structuring the northern poor-magmatic segment (28°N-21.5°N), while siliciclastic/volcanoclastic sediments and volcanic flows interpreted as SDRs characterize the southern magmatic segment (21.5°N−13°N). Tectonic and magmatic activity stopped in this crustal domain of the margin when a thick salt layer precipitated during the Middle Miocene (∼14-13 Ma). The stratigraphy of the margin then became similar between the two segments suggesting comparable post-salt subsidence and common crustal characteristics throughout the Red Sea. By characterizing its tectonostratigraphic record on a regional scale, this study tests two end-member scenarios for the tectonic evolution of the Red Sea. It also provides new insights into the tectonostratigraphic record of a rift margin system by simultaneously comparing the evolution of a magma-rich and a magma-poor segment.